1995
DOI: 10.1016/0014-5793(95)01172-b
|View full text |Cite
|
Sign up to set email alerts
|

Inverse deuterium kinetic isotope effect for peroxidation in human low‐density lipoprotein (LDL): a simple test for tocopherol‐mediated peroxidation of LDL lipids

Abstract: a-Tocopherol (a-TOH) can act as a pro-or antioxidant for isolated ubiquinol-10-free human low density lipoprotein (LDL). We demonstrate that a-TOH is a more potent prooxidant than other forms of vitamin E for LDL peroxidation initiated by mild fluxes of aqueous peroxyl radicals and low concentrations of Cu 2+. A simple deuterium exchange test shows that a-TOH switches from pro-to anti-oxidant at Cu2+:LDL ratios > 2.5. The results suggest that this test may be useful to distinguish 'inhibited' peroxidation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…In in vitro studies on copper-induced oxidation of LDL, in which the Cu 2ϩ to LDL particle ratio is at least 3, ␣-tocopherol acts as an antioxidant. 8 Our finding accords with earlier studies, in which doses of not less than 400 IU/d have lengthened the lag time. 7,37 The lag time during LT was statistically significantly shorter than that during PT.…”
Section: Discussionsupporting
confidence: 92%
“…In in vitro studies on copper-induced oxidation of LDL, in which the Cu 2ϩ to LDL particle ratio is at least 3, ␣-tocopherol acts as an antioxidant. 8 Our finding accords with earlier studies, in which doses of not less than 400 IU/d have lengthened the lag time. 7,37 The lag time during LT was statistically significantly shorter than that during PT.…”
Section: Discussionsupporting
confidence: 92%
“…Essentially, ␣-TO⅐ replaces LOO⅐ as the peroxidation chain-carrying species and unless the former radical is eliminated, a large proportion of lipid in LDL can oxidize without significant loss of vitamin E. The ␣-TO⅐ is less reactive than the LOO⅐ and as such tocopherol-mediated peroxidation represents a model of retarded lipid peroxidation relative to that caused by LOO⅐ in the absence of vitamin E. However, as ␣-TOH is highly reactive towards various oxidants, the mere presence of vitamin E in LDL renders the lipoprotein susceptible to oxidation (78,81,497,1051). This property is referred to as the phase-transfer activity of ␣-TOH.…”
Section: Role Of Vitamin E In Ldl Oxidationmentioning
confidence: 99%
“…In a number of very elegant studies Stocker and co-workers [14][15][16] have demonstrated that the antioxidant α-tocopherol may behave, under appropriate conditions, as pro-oxidant, thus paradoxically stimulating LDL oxidation promoted by a constant radical flow originating from the thermal decomposition of the azo-compound 2,2h-azobis-(2-amidino propane) hydrochloride (AAPH) or by low concentrations of copper. The pro-oxidant activity of α-tocopherol is mediated through the one-electron oxidation catalysed by peroxyl radicals or by the reductive activation of Cu(II) to Cu(I) with the concomitant formation of the α-tocopheroxyl radical which, in turn, may abstract a hydrogen atom from a polyunsaturated fatty acid in LDL, thus initiating a radical chain ultimately leading to extensive lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%